Competition between the H- and D-atom transfer channels in the H2O+ + HD reaction: reduced-dimensional quantum and quasi-classical studies. Issue 26 (26th June 2017) - Song, Hongwei; Li, Anyang; Yang, Minghui; Guo, Hua
Abstract : Good agreement is found between theoretical and experimental product branching ratios of the H2 O + + HD reaction. Abstract : The ion–molecule reaction between a water cation and a hydrogen molecule has recently attracted considerable interest due to its importance in astrochemistry. In this work, the intramolecular isotope effect of the H2 O + + HD reaction is investigated using a seven-dimensional initial state-selected time-dependent wave packet approach as well as a full-dimensional quasi-classical trajectory method on a full-dimensional ab initio global potential energy surface. The calculated branching ratios for the formation of H3 O + and H2 DO + via H- and D-transfer agree reasonably well with the experimental values. The preference to the formation of the H3 O + product observed using the experiment at low collision energies is reproduced by theoretical calculations and explained by a one-dimensional effective potential model.